[Who is nextn ; A question of turf destination ; Camiguin [videorecording] (The Probe Team, 1992)
An investigative report on the kidnapping and death of Charlene Sy and the continuous kidnapping of Filipino-Chinese in the country; and the unification of Ayala Stock Exchange and Makati Stock Exchange. Probe visits the volcanic island of Camiguin.